A Multi-agent Model to Mitigate Knowledge Loss in Continuous Academic Quality Improvement Effort - Shahrinaz, Ismail (Journal of Computing Technologies and Creative Content, 2016)
In academic management, it is a lecturer’s task to ensure that the delivery of a subject complies with the syllabus and curriculum design. In most cases, lecturers have their own way of managing their classes, aided by a personally prepared lesson plan. Usually, the contents of the lesson plans change from one semester to another, either due to a change of the lecturer in charge or improvement in delivery and assessment. However, these changes are not comprehensively tracked and documented to show improvements made on the subject, which is beneficial for curriculum design review. Consequently, subsequent curriculum review fails to consider the necessary changes for improvement in the curriculum. To mitigate the effect of this knowledge loss in tracking these changes, we propose a multi-agent knowledge management approach to conceptualise a framework in tracking and capturing lecturers’ initiatives for improving the course delivery, and this can be further integrated as the change process in CQI for curriculum design review. Quantitative and qualitative analysis approaches are deployed to identify the change and update processes that lecturers adopt in updating their course delivery. This is followed by a study in multi-agent system to be applied in animating the processes. A knowledge management framework is then synthesised by considering the dynamics of the change processes to manifest the tracking and capturing of new knowledge in course delivery. The outcome of this research is a model of knowledge management process that captures the knowledge of course delivery changes made by lectures. The outcome is significance in contributing to the CQI in curriculum design review.